Morphology and carrier mobility of high-B-content BxAl1−xN ternary alloys from an ab initio global search. Issue 31 (27th July 2022) - Qi, Zhanbin; Shi, Zhiming; Zang, Hang; Ma, Xiaobao; Yang, Yuxin; Jia, Yuping; Jiang, Ke; Sun, Xiaojuan; Li, Dabing
Abstract : An energetically favorable B x Al1− x N structure from wurtzite to hexagonal for the new B@50% polymorph is found with a space group of Ccm 21 . Abstract : The excellent properties of III-nitrides and their alloys have led to significant applications in optoelectronic devices. Boron, the lightest IIIA group element, makes it possible to extend the flexibility of III-nitride alloys. However, both B x Al1− x N and B x Ga1− x N ternary alloys suffer from poor material quality during crystal growth, their B contents in experimental reports are no higher than 22%, and the underlying mechanism is still unclear. Herein, ab initio global calculation by particle swarm optimization combined with density functional theory is carried out to identify the ground structures of B x Al1− x N alloys with different B contents ( x = 0.25, 0.5, and 0.75). Furthermore, the electronic properties and intrinsic carrier mobility are studied. For B0.25 Al0.75 N and B0.75 Al0.25 N, quasi-wurtzite and quasi-hexagonal structures are energetically favourable, respectively, indicating a wurtzite-to-hexagonal structural transition due to the three-coordinated B atoms being incorporated into the lattice. When the B content is 50%, B0.5 Al0.5 N shows a ten-membered ring structure with an indirect bandgap of 3.52 eV and strong anisotropy of mobility. Our results uncover the mechanism of the structural and electronic property evolution with B content and pave a route for the application of B-containing III-nitride alloys.